these two questions are to be factored completely but i have no idea how to factor them
A great deal of algebra is pattern recognition. The ability to look at an expression and see a pattern. Not unlike hearing the first two bars of a song and recognizing what it is. In your first problem the key is to look at
Let z = x - 4y, then
= z 2 - 3z - 4
= (z - 4)(z + 1)
For the second problem you know how to factor a sum of cubes. But (x 2) 3 = x 6 and (y 2) 3 = x 6, and thus
To return to the previous page use your browser's back button.